Singapore : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
Singapore's recent economic performance has been impressive, underpinned by prudent macroeconomic management. Economic activity remains strong despite a softening in external demand. On the demand side, domestic demand strengthened driven by private consumption and investment while net exports were broadly unchanged during the first half of 2007. It has been noted that the exchange-rate-based monetary policy framework has served Singapore's small, open economy well. As inflation expectations are well anchored, they agreed that the present monetary policy stance of targeting a gradual nominal effective exchange rate appreciation remains appropriate.